Depositional and diagenetic environments of the Dhosa Oolite member (Oxfordian), Kachchh Basin, India: Implications for the origin and occurrence of the ooids and their correlation with the global Fe-oolite peak - Ramkumar, Muthuvairavasamy; Alberti, Matthias; Fürsich, Franz; Pandey, Dhirendra Kumar (On a sustainable future of the Earth's natural resources, 2013)
Based on bio and lithofacies characteristics and occurrences of hardground surfaces, oolites, iron crusts and shell lags, the Dhosa Oolite member (DOM) of Kachchh basin, India is considered to be equivalent of Fe-oolitic deposits of many European sections that formed during the Callovian-Oxfordian eustatic sea-level maximum. Lithofacies and textural and diagenetic characteristics revealed that the ooids of DOM were originally calcitic and, after initial deposition, experienced diagenesis under reducing conditions followed by exhumation, multiple episodes of transport and final burial in low-energy areas. High-frequency sea-level cycles occurred during the deposition of the Dhosa Oolite member that exposed the oolitic and other sediments to diagenesis in shallower marine regions and with significant dissolution-precipitation in marine-phreatic, burial, meteoric-phreatic and vadose zones. Owing to the synsedimentary lithification at the final burial site and low-magnesian calcitic precursors of bioclasts and ooids, the micritic matrix and marine cement spars preserved their morphologic integrity until dissolution in the meteoric-vadose zone. Subaerial exposure of the sediments following sea-level retreat had subjected them to intense meteoric-phreatic zone diagenesis that had morphologically and mineralogically transformed the susceptible carbonate components. Change in groundwater table had exposed these carbonate components to meteoric-vadose and oxygenated waters of the meteoric-phreatic zone, caused oxidation, subjected them to leaching of Fe and silicification, that might have resulted in distinct color to the rocks, iron crusts, and iron oxide coating. Independent analyses of selected ooids under EPMA compositional mapping also revealed the original calcareous nature of the ooids, enrichment of Fe and latter Si in selective portions and layers of ooids. These observations suggest precipitation of low-magnesian calcitic ooids on shallow, coastal ooid shoals → multiple episodes of transport → deposition, lithification, Fe enrichment in susceptible parts of ooids and bioclasts, and iron-mineral replacement under sub-oxic condition → exhumation, offshore transport, deposition in low-energy areas → neomorphic alteration in the marine-phreatic zone → selective dissolution and stabilization of calcite in the marine-burial zone → complete dissolution in the meteoric-vadose zone, development of mouldic porosity and its infilling by ferroan equant calcitic spar in the meteoric-phreatic zone → exposure to oxidizing waters in the meteoric-vadose and -phreatic zones, destructive neomorphism, selective silicification of portions of ooids, oxidation of iron in ferroan calcitic spars and iron-rich clay present in the rock → iron oxide coating → Ca-Fe-Si-ooid formation as the paragenetic sequence. The results suggest that these ooids should not be correlated with worldwide occurrences of Fe-oolites per se for two reasons, namely, the complete erosion of the coeval stratigraphic record of the worldwide Fe-oolite peak, and the originally calcite nature of the ooids. It is also brought to light that while the ooids were formed during a transgressive phase, final burial of ooids occurred during regression. However, the sea-level rise resumed towards the top of the DOM resulting in formation of shell lags, hardground surfaces, and/or maximum flooding surfaces, etc. The top of the DOM is represented by karstic surfaces, dissolution-related collapse structures, and mixing of younger sediments.
UnivIS-Import:2017-12-18:Pub.2013.nat.dgeo.IGM.LP.deposi
Keywords: Lithification; Sandstone; Compaction; Silt Holocene